Menelusuri Jejak Tan Sim Tjong dan Sejarah Kota Bandoeng - Tjahjadi, Bambang; Dharmadji, Adji; Subrata, Charles; Tjahjadi, Wishnu (Zenit, 2015)
“Simtjong“ Alley at the Citepus district of Bandung is named after a Chinese Tan Sim Tjong. He and his family lived next to this alley in a very typical and stately house, built on a large property. Around the end of the 19th Century, Tan Sim Tjong moved to Jalan Cibadak, in which he stayed until he passed away (1929), so did his descendants until the fourth generation. As a „peranakan“ (Chinese born Indonesian), Tan Sim Tjong was against the Chinese tradition by supporting the marriage of his son and a Chinese woman with the same family name (she). During his lifetime, Tan Sim Tjong also promoted the improvement of education for the Chinese children in Bandung. In June 2014, one of his descendants rediscovered his delapidated gravestone in the village of Sentiong Cijerah. Hence, a project is proposed for the artifacts in order to maintain the history and local wisdom of the people in Bandung.Keywords: Tan Sim Tjong, Citepus, Simtjong Alley, geneology, “peranakan”, marriage within clan, THHK Bandoeng, tomb Sentiong, Cijerah.